Uncanny Resemblances – Prov 9 as an Introduction to Proverbial Thinking - Ehmer, Yannik (Zeitschrift für die alttestamentliche Wissenschaft, 2025)
This article suggests that Prov 9 serves as an introduction to Prov 10:1-22:16, »dramatizing« it as competing banquets of Wisdom and Folly. Proverbial knowledge allows to discern between the invitations of the two voices. It enables the student of wisdom to navigate a life amidst ambiguities and uncanniness. Proverbial thinking teaches a phenomenological and critical hermeneutics that takes response-ability--i.e. the ability to respond--seriously. The uneducated person (פְּתִי) must learn to which call they should respond. Folly/chaos is therefore an integral part of Wisdom/order.